1996
DOI: 10.1007/bf01408531
|View full text |Cite
|
Sign up to set email alerts
|

Chronic sorrow: A content analysis of parental differences

Abstract: Sixty-eight mothers and 64 fathers of children with a neural tube defect responded to a questionnaire about chronic sorrow. Mothers reported a mood state change in very intense category from more pessimistic at time of diagnosis to more optimistic at current time. Fathers, although indicating a mood change in the very intense category to more optimistic, also had more pessimistic responses. Parental similarities and differences were also reported in both times and events that triggered the sorrow response. Cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
3
0
2
Order By: Relevance
“…In addition, women also tend to be more emotionally aware. Reduced involvement of care might be interpreted to reduced impact; a great factor contributing to the existence of chronic sorrow …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, women also tend to be more emotionally aware. Reduced involvement of care might be interpreted to reduced impact; a great factor contributing to the existence of chronic sorrow …”
Section: Discussionmentioning
confidence: 99%
“…Reduced involvement of care might be interpreted to reduced impact; a great factor contributing to the existence of chronic sorrow. 16 Huang et al 17 indicated that the caregivers of family members with schizophrenia in Taiwan adopted social support, provided first by other family members and then by friends and neighbors, to achieve social coping. While most of the participants expressed that they received the lowest level of support from professionals, they indicated that professionals were their most valued source of support.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is necessary to identify different aspects of families’ sorrow in confronting this chronic disease. Previous studies have emphasized the effects of gender differences on chronic sorrow among the caregivers of children: That is, the condition has higher prevalence in women (Hodbell & Deatrick, 1996). Therefore, this study aimed to determine the level and dimensions of chronic sorrow in mothers of children with cancer and to evaluate its relationship with some demographic characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Συχνά και σε αυτές τις περιπτώσεις η πιθανότητα διάλυσης της οικογένειας είναι μια πραγματική απειλή. 68,69,70,71 Θάνατος νεογνού Στις περιπτώσεις θανάτου του νεογνού, μεγαλύτερο πρόβλημα φαίνεται να υπάρχει στην αποδοχή του γεγονότος. Έντονα είναι συχνά εδώ τα συναισθήματα της άρνησης και της αμφιβολίας, ιδιαίτερα όταν στο ζευγάρι δεν δόθηκε η δυνατότητα να δει και να κρατήσει το νεκρό νεογνό.…”
Section: ψυχολογία γονέων μετά από γέννηση παιδιού με ανωμαλία χωρίς προϋπάρχουσα προγεννητική διάγνωσηunclassified
“…Έντονα είναι συχνά εδώ τα συναισθήματα της άρνησης και της αμφιβολίας, ιδιαίτερα όταν στο ζευγάρι δεν δόθηκε η δυνατότητα να δει και να κρατήσει το νεκρό νεογνό. 68,69,70,71 Για να προσφερθεί η κατάλληλη ψυχολογική υποστήριξη πρέπει πρώτα να γίνει ψυχοκοινωνική εκτίμηση του ασθενή (psychosocial assessment). Η στρατηγική που θα ακολουθήσει ο σύμβουλος γενετικής για να υποστηρίξει ψυχολογικά τον ασθενή, εξαρτάται κατά πολύ από αυτή την εκτίμηση.…”
Section: ψυχολογία γονέων μετά από γέννηση παιδιού με ανωμαλία χωρίς προϋπάρχουσα προγεννητική διάγνωσηunclassified